Photocatalytic Properties of Cupric Oxide Nanosheets Prepared by a Low-Temperature Soft Solution Processing - Xu, Ling; Xu, Hai-Yan; Liu, Chang-Ling; Wu, Shi-Biao; Wang, Xu-Dong; Song, Xiao-Jie; Wang, Feng (Asian Journal of Chemistry, 2012)
Cupric oxide nanosheets with uniform thickness less than 20 nm have been prepared by a low-temperature soft solution processing simply using Cu(NO3)2, NH4Cl and ammonia instead of any toxic and dangerous reagents. The results illustrate that well defined CuO nanosheets can be obtained at 80 ºC for 1 h with pH of 10. The prepared CuO nanosheets show quite good photocatalytic activity under irradiation of solar simulator lamp. The photocatalytic degradation is strongly dependent on solution pH, and H2O2 is quite favorable for degradation of methyl orange in CuO nanosheets photocatalytic system.